Современное состояние популяции большого баклана на территории Дунайского биосферного заповедника - Яковлев, М.В. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2008)
In total 264 bird species are noted within the area of the Danube Biosphere Reserve (Zhmud, 2004; own data). The reserved area is of great importance for the Cormorant (Phalacrocorax carbo). The Cormorant is a common breeding and common wintering species in the Danube Biosphere Reserve. It nests solely on the willow trees, forming one-three colonies in the southern part of Danube Delta, on adjoining Lebedinka and Kurilskie Islands. Approximately after every 5 years the colony moves from one place to another due to degradation and death of the trees where birds build their nests, because of the aggressive influence of their excrements.